Prinsip Kejujuran Dalam Usaha: Menelaah Materi tentang Prinsip Kejujuran dalam Usaha - Maghudi, Muhammad Imam; M, Misbahuddin; Ridwan, M. Saleh (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Honesty is one of the important things that must be done by parties carrying out transactions in business ventures. A person who is honest in his soul has spiritual values that reflect an attitude of siding with the truth, commendable morals, and responsibility in carrying out his duties and work, so that he appears as a person of integrity who has a commendable and complete personality. Honesty is a pearl of morals that will place a person in a noble position. An honest business person will keep his balance, telling the good and bad of the goods he sells. From a buying and selling relationship that is based on honesty, trust will emerge between the seller and the buyer or between the service provider and the service user. This belief is one way to ensure that business is carried out in accordance with Islamic sharia, which is the most basic of all relationships and transactions in business activities.